2017
DOI: 10.1007/s00268-017-4416-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Coronary Heart Disease Risk Decreases in Obese Patients After Laparoscopic Sleeve Gastrectomy

Abstract: Laparoscopic sleeve gastrectomy is efficient not only in the reduction of obesity and its related comorbidities but also in decreasing the long-term coronary event risk. Early intervention for the high-risk group is strongly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Thus early bariatric intervention for the high-risk groups is strongly recommended by the authors. 10 Our patients did not have increased risk of coronary heart disease but three of our patients had a significant improvement in serum cholesterol and triglyceride levels 6months postoperatively. As far as glycemic control and diabetes are concerned, data for benefits after sleeve gastrectomy are still conflicting, suggesting the need for further studies.…”
Section: Effects Of Sleeve Gastrectomymentioning
confidence: 51%
“…Thus early bariatric intervention for the high-risk groups is strongly recommended by the authors. 10 Our patients did not have increased risk of coronary heart disease but three of our patients had a significant improvement in serum cholesterol and triglyceride levels 6months postoperatively. As far as glycemic control and diabetes are concerned, data for benefits after sleeve gastrectomy are still conflicting, suggesting the need for further studies.…”
Section: Effects Of Sleeve Gastrectomymentioning
confidence: 51%
“…When compared with the study population of Blanco et al was reported [26]. Second, there were differences in the calculation methods of the risk scores.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, studies on which kind of bariatric surgery would be more beneficial in improving the CVD score are rare. Several studies reported that laparoscopic Roux-en Y gastric bypass (LRYGB), laparoscopic sleeve gastrectomy (LSG), and laparoscopic adjustable gastric banding reduced the CVD risk score; however, most of them were noncomparative studies [12,[24][25][26] and only few studies directly compared LSG and LRYGB [13][14][15]27].…”
Section: Introductionmentioning
confidence: 99%